How college students succeed making meaning across disciplinary perspectives - Bowman, Nicholas A. 1979- (Stylus Publishing, LLC, 2022)
"The purpose of this book is to bring together in a single volume the extensive knowledge on college student success. It includes seven chapters from authors who each synthesize the literature from their own field of study, or perspective"--